IoT Based Early Flood Detection System with Arduino and Ultrasonic Sensors in Flood-Prone Areas - Muhammad Darwis; Hafiizh Asrofil Al Banna; Setiawan Restu Aji; Dinda Khoirunnisa; Nakia Natassa (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2023)
IoT is one of the focuses of application development carried out by various developers today. The aim is to enable various devices and work independently to meet the various needs of their users. The flood early warning system is one of the much-needed IoT-based applications, enabling users to quickly obtain water level information in an area. This application can help people to be more aware of flood disasters, especially during the rainy season. This research develops a flood early warning system application by utilizing Arduino and ultrasonic sensors installed in flood-prone areas. The sensor is used to measure the water level at a time based on the distance from the water surface to the sensor. When the distance between the water surface and the sensor is less than or equal to the set threshold, the sensor will send data and alerts to the user via email. This research applies the IoT design and development method. In addition, this research also used the C and Python programming language for application prototypes and the MySQL database to store the data. the application in this study was tested using the blackbox method and the results showed that all application functions could run properly.